2023
DOI: 10.1186/s40748-023-00149-1
|View full text |Cite
|
Sign up to set email alerts
|

Association of maternal nationality with preterm birth and low birth weight rates: analysis of nationwide data in Japan from 2016 to 2020

Abstract: Background The rate of low birth weight or preterm birth is known to vary according to the birth place of mothers. However, in Japan, studies that investigated the association between maternal nationalities and adverse birth outcomes are few. In this study, we investigated the association between maternal nationalities and adverse birth outcomes. Methods We obtained live birth data from the Vital Statistics 2016–2020 of the Ministry of Health, Labo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…When it comes to nationality, prior research conducted across various countries has consistently demonstrated that maternal nationality influences the occurrence of PTB. Results of a study conducted in Japan showed that nationality had a statistically significant impact on the relative risk of PTB, with Filipino and Brazilian mothers showing the highest risks, while Korean and Chinese mothers had lower relative risks compared to Japanese mothers [23]. Another study in England and Wales spanning from 2006 to 2012 also revealed ethnic disparities in PTB rates.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…When it comes to nationality, prior research conducted across various countries has consistently demonstrated that maternal nationality influences the occurrence of PTB. Results of a study conducted in Japan showed that nationality had a statistically significant impact on the relative risk of PTB, with Filipino and Brazilian mothers showing the highest risks, while Korean and Chinese mothers had lower relative risks compared to Japanese mothers [23]. Another study in England and Wales spanning from 2006 to 2012 also revealed ethnic disparities in PTB rates.…”
Section: Discussionmentioning
confidence: 98%
“…Additional determinants encompass neighbourhood income, family structure, race/ethnicity, place of residence, and wealth. These socioeconomic factors have been included as variables in several previous studies that have demonstrated an association of poorer pregnancy outcomes with lower SES [17][18][19][20][21][22][23][24]. The links between SES and adverse pregnancy outcomes are observed even in prosperous countries with a universal healthcare system suggesting that the associations observed may not be attributable to the type of prenatal care received [12,[25][26][27].…”
Section: Introductionmentioning
confidence: 99%